- pericardiocentesis in diagnosis and treatment of pericardial cardiac wounds - Perdomo, Roberto (Cirugía del Uruguay, 1971)
This is the case history of a cardiopericardic wound with temponment, treated by conservative methods through evacuation pericardiocentesis. The value of pericardiocentesis in the diagnosis of cardiopericardic wounds and in the initial emergency treatment for the hemopericardio is discussed, as well as the possibility of using this method as definite conservative treatment in certain selected cases.